Hydrogen-donated thermal upgrading of Venezuela extra-heavy oil: identifying the role of hydrogen donor. (18th March 2020) - Chen, Qiang; Yin, Menghui; Zhang, Lingling; Liu, He; Qin, Zhihong; Wang, Zongxian
Abstract: A natural hydrogen donor, i.e., a subfraction of the coker gas oil, was used in thermal upgrading of the Venezuela extra-heavy oil. The role of hydrogen donor was quantitatively studied by a combination of thermogravimetric analysis and differential scanning calorimetry. The hydrogen donation was clearly evidenced and reliably evaluated by comparing the experimental and calculated thermal parameters. The mutual interactions between the heavy oil and the hydrogen donor extended the coke induction period (from 19 to 25 min), inhibited the thermal evaporation of the hydrogen donor, and resulted in a stronger endothermic effect in the pyrolysis stage.